Antibacterial activity and action mechanism of a novel chitosan oligosaccharide derivative against dominant spoilage bacteria isolated from shrimp Penaeus vannamei. (1st February 2022) - Wei, X.‐Y.; Xia, W.; Zhou, T.
Abstract: With the aim of exploring the potential application of a novel chitosan oligosaccharide derivative (COS‐All‐Tio) in shrimp preservation, six dominant spoilage bacteria in the spoiled shrimp ( Penaeus vannamei ) were isolated and identified as Shewanella putrefaciens (RMS1), S . putrefaciens (S2), Pseudomonas weihenstephanensis (P1), P. gessardii (P2), Aeromonas bestiarum (A1) and Aeromonas molluscorum (A2). The antibacterial effect of COS‐All‐Tio against the six bacterial isolates were studied. Bacterial inhibition zone determination, and minimum inhibitory concentration and minimum bactericidal concentration assays indicated that the antibacterial activity of COS‐All‐Tio was greatly improved when compared to that of chitosan oligosaccharide (COS). The antibacterial mechanism investigation against S. putrefaciens (RMS1) revealed that COS‐All‐Tio could inhibit bacterial growth by influencing of membrane integrity. Such disturbance of membrane structure resulted in the leakage of intracellular substance of the bacteria. A strong synergistic antibacterial effect against S. putrefaciens (RMS1) was observed when COS‐All‐Tio was used in combination with food preservatives (e.g. ε‐polylysine hydrochloride). Therefore, COS‐All‐Tio might have potential in shrimp preservation.